SUPERVISI AKADEMIK KEPALA MADRASAH DALAM PENINGKATAN MUTU PEMBELAJARAN GURU DI MTS MADRASATUL QUR'AN TEBUIRENG - Fikri Nur Fuad; Muhammad Al-Fatih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Within madrasah settings, academic supervision serves as a strategic mechanism whose primary purpose is the sustained professional growth of teachers, thereby directly contributing to the overall improvement of instructional quality. The madrasah principal holds a pivotal role in this process, functioning as an academic supervisor with comprehensive responsibility for planning, executing, and assessing the learning process in alignment with prevailing educational quality standards. The present study seeks to describe and analyze how academic supervision by the madrasah principal is carried out in improving the quality of teachers' instruction at MTs Madrasatul Qur'an Tebuireng, while also examining the facilitating and constraining factors involved in its implementation.A qualitative methodology with a case study design was employed in conducting this research. Data were gathered through in-depth interviews, direct observation, and documentation, with the madrasah principal, vice principal for curriculum affairs, and classroom teachers serving as the primary research subjects. The analytical process followed three sequential stages: data reduction, data display, and conclusion drawing. To ensure data trustworthiness, both source triangulation and method triangulation were applied.The results demonstrate that academic supervision at MTs Madrasatul Qur'an Tebuireng proceeds systematically through three interconnected stages: well-structured supervisory planning, supervisory execution grounded in collaborative and humanistic principles, and follow-up measures encompassing guidance, mentoring, and instructional evaluation. This supervisory process exerts a demonstrably positive influence on instructional quality, manifested through enhanced lesson planning, greater diversity in teaching methods, and strengthened teacher professionalism. Among the enabling factors are the principal's strong commitment, a supportive institutional work culture, and the receptiveness of teachers, whereas limiting factors include insufficient time allocation and heavy administrative demands. These findings affirm that academic supervision, when conducted effectively and on a sustained basis, makes a substantial contribution to raising the standard of learning in madrasahs.